The mucin-degradation strategy of Ruminococcus gnavus: The importance of intramolecular trans-sialidases. (3rd July 2016) - Crost, Emmanuelle H.; Tailford, Louise E.; Monestier, Marie; Swarbreck, David; Henrissat, Bernard; Crossman, Lisa C.; Juge, Nathalie
ABSTRACT: We previously identified and characterized an intramolecular trans -sialidase (IT-sialidase) in the gut symbiont Ruminococcus gnavus ATCC 29149, which is associated to the ability of the strain to grow on mucins. In this work we have obtained and analyzed the draft genome sequence of another R. gnavus mucin-degrader, ATCC 35913, isolated from a healthy individual. Transcriptomics analyses of both ATCC 29149 and ATCC 35913 strains confirmed that the strategy utilized by R. gnavus for mucin-degradation is focused on the utilization of terminal mucin glycans. R. gnavus ATCC 35913 also encodes a predicted IT-sialidase and harbors a Nan cluster dedicated to sialic acid utilization. We showed that the Nan cluster was upregulated when the strains were grown in presence of mucin. In addition we demonstrated that both R. gnavus strains were able to grow on 2, 7-anyhydro-Neu5Ac, the IT-sialidase transglycosylation product, as a sole carbon source. Taken together these data further support the hypothesis that IT-sialidase expressing gut microbes, provide commensal bacteria such as R. gnavus with a nutritional competitive advantage, by accessing and transforming a source of nutrient to their own benefit.